Regioselective biooxidation of (+)-valencene by recombinant E. coli expressing CYP109B1 from Bacillus subtilis in a two-liquid-phase system - Schmid Rolf D (Microbial Cell Factories, 2009)
Abstract Background (+)-Nootkatone (4) is a high added-value compound found in grapefruit juice. Allylic oxidation of the sesquiterpene (+)-valencene (1) provides an attractive route to this sought-after flavoring. So far, chemical methods to produce (+)-nootkatone (4) from (+)-valencene (1) involve unsafe toxic compounds, whereas several biotechnological approaches applied yield large amounts of undesirable byproducts. In the present work 125 cytochrome P450 enzymes from bacteria were tested for regioselective oxidation of (+)-valencene (1) at allylic C2-position to produce (+)-nootkatone (4) via cis- (2) or trans-nootkatol (3). The P450 activity was supported by the co-expression of putidaredoxin reductase (PdR) and putidaredoxin (Pdx) from Pseudomonas putida in Escherichia coli. Results Addressing the whole-cell system, the cytochrome CYP109B1 from Bacillus subtilis was found to catalyze the oxidation of (+)-valencene (1) yielding nootkatol (2 and 3) and (+)-nootkatone (4). However, when the in vivo biooxidation of (+)-valencene (1) with CYP109B1 was carried out in an aqueous milieu, a number of undesired multi-oxygenated products has also been observed accounting for approximately 35% of the total product. The formation of these byproducts was significantly reduced when aqueous-organic two-liquid-phase systems with four water immiscible organic solvents – isooctane, n-octane, dodecane or hexadecane – were set up, resulting in accumulation of nootkatol (2 and 3) and (+)-nootkatone (4) of up to 97% of the total product. The best productivity of 120 mg l-1 of desired products was achieved within 8 h in the system comprising 10% dodecane. Conclusion This study demonstrates that the identification of new P450s capable of producing valuable compounds can basically be achieved by screening of recombinant P450 libraries. The biphasic reaction system described in this work presents an attractive way for the production of (+)-nootkatone (4), as it is safe and can easily be controlled and scaled up.